2023
DOI: 10.3390/jrfm16040235
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Determinants of Credit Risk Management and Their Relationship with the Performance of Commercial Banks in Nepal

Abstract: In recent years, after the global financial crisis, the issue of credit risk management has received increased attention from international regulators. Credit risk management frameworks are often not sufficiently integrated within the organization, there is no unified approach, and there is no holistic view of all risks. Likewise, where they exist, sound risk management practices have helped institutions to weather financial crises better than others. Therefore, the current study aimed to examine the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…The study from (Bhatt et al, 2023) the results of market risk analysis research have a significant effect on credit risk management. The results showed that credit risk management mediates the relationship between environmental risk, credit rating measurement, market risk analysis, and commercial bank performance.…”
Section: Resultsmentioning
confidence: 99%
“…The study from (Bhatt et al, 2023) the results of market risk analysis research have a significant effect on credit risk management. The results showed that credit risk management mediates the relationship between environmental risk, credit rating measurement, market risk analysis, and commercial bank performance.…”
Section: Resultsmentioning
confidence: 99%
“…Many uncertified risk management employees also contribute to weak credit risk identification and management processes. Tien and Nguyen (2023) state that good credit risk identification and management affect credit performance and help banks to control and reduce credit risk (Mburu et al, 2020;Akomeah et al, 2020;Bhatt et al, 2023). The policy of credit granting is good enough, except for the absence of a final risk grading system, if the implementation operates properly.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investing in robust credit risk management to increase the likelihood of default avoidance is crucial for banks to successfully and safely maintain their financial position (Rakhaev, 2020). It is well-supported by research, and many studies have unfolded on how effective credit risk management is a function of bank performance (Bhatt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%